1985
DOI: 10.1007/bf00910641
|View full text |Cite
|
Sign up to set email alerts
|

Main and interaction effects of metallic toxins on classroom behavior

Abstract: This study investigated the relationships of metal levels and metal combinations to children's classroom behavior. Hair-metal concentrations of lead, arsenic, mercury, cadmium, and aluminum were determined in 80 randomly selected elementary-age children, who were also rated by their classroom teacher on the Walker Problem Behavior Identification Checklist (WPBIC). Parents were interviewed to control for confounding variables that may have affected behavioral development. Regression analysis indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Also previous studies have investigated correlations among Pb, Cd, and trace elements in hair, teeth, and nails, but ours is the fi rst to have assessed such associations in meconium. High Pb concentration both decreased Fe concentration and altered Fe/Cu and Fe/Zn ratios [27] . Other research has demonstrated a signifi cant negative correlation between Cd and Zn in blood, but a signifi cant positive correlation between Cd and Zn in seminal plasma [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Also previous studies have investigated correlations among Pb, Cd, and trace elements in hair, teeth, and nails, but ours is the fi rst to have assessed such associations in meconium. High Pb concentration both decreased Fe concentration and altered Fe/Cu and Fe/Zn ratios [27] . Other research has demonstrated a signifi cant negative correlation between Cd and Zn in blood, but a signifi cant positive correlation between Cd and Zn in seminal plasma [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In cohort studies, Thatcher et al (75,76) reported that the concentration of cadmium in hair was significantly inversely related to adjusted IQ scores, particularly verbal IQ, and to visual evoked potentials; (77) and Marlowe and colleagues (78,79) reported associations between increased hair cadmium and children's performance on visual-motor tasks. Marlowe et al (80) also reported that lead and cadmium acted synergistically in impair children's classroom behavior.…”
Section: Neurotoxicity Of Cadmiummentioning
confidence: 99%
“…These data support other recent studies that have correlated increased hair metal levels with mental retardation (Marlowe, Folio, Hall, & Errera, 1982;Marlowe, Errera, & Jacobs, 1983). Studies of general school populations have also linked increasing hair metal levels and their interactions to decrements in psychometric intelligence (Thatcher, Lester, McAlaster, & Horst, 1982;Moon, Marlowe, & Errera, in press), adaptive behavior (Marlowe, Cossairt, Moon, & Errera, 1985), and academic achievement (Moon, Marlowe, Stellern, & Errera, 1985).…”
Section: Discussionmentioning
confidence: 98%